Penyimpangan Maksim Kesantunan Berbahasa Konten “POV Gen Z” dalam Sosial Media TikTok dan Implikasinya Terhadap Mahasiswa Universitas Muslim Nusantara Al-Washliyah Medan - Siregar, Ernia Sahara; Pulungan, Rosmilan (Universitas Islam Sumatera Utara, 2025)
This study analyzes the violation of politeness maxims in 15 TikTok “POV Gen Z” contents themed around teachers and examines their implications for students of Indonesian Language and Literature Education (PBSI) at Universitas Muslim Nusantara Al-Washliyah Medan. The research focuses on identifying the most frequent types of violations and their social as well as academic impacts. Using a descriptive qualitative method, data were collected through observation of 15 TikTok videos with the hashtag “POV Gen Z as a teacher” and in-depth interviews with PBSI students active on TikTok. Participants were selected based on follower count and level of engagement, while the research was conducted in classrooms and the university library. Findings revealed 24 cases of politeness maxim violations: tact (11), agreement (6), generosity (2), approbation (1), modesty (2), and sympathy (2). The language in these contents was largely informal and disparaging, albeit presented humorously, reflecting Gen Z’s expressive communication style driven by virality, self-expression, and social critique. Implications for PBSI students were significant, with perceptions ranging from viewing the violations as creativity to concerns about their impact on teacher image and language norms. Despite diverse views, most students emphasized the importance of politeness principles in formal contexts. This study contributes to politeness theory in social media discourse and supports the development of digital literacy.